Analisis Analisis Kekuatan Sambungan Angel Corner pada Alumunium Profile 2020 untuk Rangka Printer 3D Logam - Yupi Andrian; Deri Teguh Santoso; Uji Burrahman; Afrialdy Ilham Almanyansyah; Rangga Surya Syahputra (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2026)
This study analyzes the structural performance of angel corner joints in aluminium profile 2020, which serve as critical connectors in the frame of a metal 3D printer based on MIG welding. The objective is to evaluate the influence of material variation on stress distribution, deformation, and safety factor using the Finite Element Method (FEM) in ANSYS. Three materials were examined: Aluminium Alloy 6061-T6, Structural Steel S355, and Stainless Steel 316L. A three-dimensional CAD model of the corner joint was developed and subjected to a static load of 150 N to represent realistic operational conditions. The results indicate that maximum von Mises stress for all materials remains below their respective yield strengths, confirming elastic behavior. Structural Steel S355 produced the smallest deformation (0.065 mm) and the highest safety factor (4.34), while Aluminium Alloy 6061-T6 exhibited larger deformation (0.145 mm) and a lower safety factor (2.59), but still within safe limits. Stainless Steel 316L demonstrated intermediate performance with a safety factor of 2.26 and deformation of 0.102 mm. These findings highlight that material selection significantly affects stiffness and safety margin of the frame. Structural Steel S355 is recommended when strength and stability are prioritized, whereas Aluminium Alloy 6061-T6 may be considered when lightweight construction is required.